Spiritual concert in the work of Ukrainian composers: The processes of individualization of the genre archetype - Husarchuk, Tetiana V.; Severynova, Maryna Yu.; Derevianchenko, Olena O.; Putiatytska, Olha V.; Hnatiuk, Larysa A. (Linguistics and Culture Review, 2021)
The last decades in the post-Soviet space are characterized by spiritual searches, growing interest in spiritual heritage, in musical art – the blossoming of spiritual creativity, in music science – by increasing attention to genres of spiritual music. The relevance of the problem stated in the article is caused by the need to highlight the development of the genre of spiritual choir concert as an exceptionally important and illustrative for Ukrainian musical art. The purpose of the research is to reveal evolutional tendencies of the genre archetype throughout its history of presence in Ukrainian music art. The leading method of this investigation is a genre-style method, which provides detection of different levels of transformations of genre invariant, connected to historical and style conditions and peculiarities of individual styles of composers. The results of the study can be useful to researchers of choral art and choral conductors, can be used in the pedagogical process – in educational courses on music history, choral literature, music culturology.